2017
DOI: 10.1039/c7ra04386d
|View full text |Cite
|
Sign up to set email alerts
|

Internally plasticized PVC materials via covalent attachment of aminated tung oil methyl ester

Abstract: We developed an internal plasticizer of aminated tung oil methyl ester for the production of non-migration, phthalate-free flexible and internally plasticized poly(vinyl chloride) (PVC) materials. The chemical structure of the synthesized aminated tung oil methyl ester and the internally plasticized PVC materials were characterized. The obtained internally plasticized PVC materials presented a lower glass transition temperature (T g ) and were more flexible than pure PVC. The thermal stability of internally pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 46 publications
3
37
0
Order By: Relevance
“…Covalent attachment of plasticizers to PVC chains, internal plasticization, is an effective way to avoid migration of plasticizers from the PVC. Reports of internal plasticization using sulfide [22][23][24][25][26] and amine 27,28 attachments to PVC demonstrate impressive reduction of the T g values. However, sulfide linkers are susceptible to oxidation, leading to both discoloration and degradation over time.…”
mentioning
confidence: 99%
“…Covalent attachment of plasticizers to PVC chains, internal plasticization, is an effective way to avoid migration of plasticizers from the PVC. Reports of internal plasticization using sulfide [22][23][24][25][26] and amine 27,28 attachments to PVC demonstrate impressive reduction of the T g values. However, sulfide linkers are susceptible to oxidation, leading to both discoloration and degradation over time.…”
mentioning
confidence: 99%
“…The thermal degradation of PVC materials has been widely studied. According to the literature, there are two different thermal degradation stages for PVC materials. The first stage is assigned to the dechlorination process when a large amount of HCl is released and the PVC material loses most of its weight.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Jia et al . reported that phosphorus‐containing castor oil based derivatives, triethyl citrate plasticizer, mannich base of cardanol butyl ether and waste cooking oil methyl ester, aminated tung oil methyl ester and monooctyl phthalate derivative were covalently linked to the PVC matrix to produce internally plasticized PVC materials without plasticizer migration. Phosphorus‐containing castor oil based derivatives grafted on PVC chains not only formed plasticized PVC materials but also enhanced the flame retardancy of the PVC materials .…”
Section: Introductionmentioning
confidence: 99%
“…The second stage at above 400 o C is corresponded to cross linking containing C = C bond. The process of thermal degradation of polyenes involves cyclization and splitting of chains [26][27][28] . The DTG curves of all PVC blends also presents two thermal degradation processes.…”
Section: Melts Blends Torque Evaluationmentioning
confidence: 99%